Maya543
contestada

Which binomial must be subtracted from (10r-7) so that the difference of the 2 polynomials is (93r+12)?

Respuesta :

aachen

First binomial expression is A = (10r - 7).

Let's assume second binomial expression is B.

and third binomial expression is C = (93r + 12).

According to given question, A - B = C.

To find B, we can subtract C from A such that;

B = A - C

B = (10r - 7) - (93r + 12)

Distributing negative sign and removing parentheses;

B = 10r - 7 - 93r - 12

Combining like terms;

B = (10r - 93r) + (-7 -12)

B = (-83r) + (-19)

B = -83r -19

Hence, second binomial expression would be B = (-83r -19).